Ensila Plus and Cold-flo additives for corn silage - Bolsen, K.; Ilg, H. (Kansas State University. Agricultural Experiment Station, 2011)
Enzyme (Ensila Plus) and non-protein nitrogen (Cold-flo) silage additives were evaluated with whole-plant corn silage. Cold-flo increased ensiling temperatures 6 to 80 F during the first week. Growing steers fed Ensila Plus, Cold-flo, or control + SBM silage rations had similar performances, and better than steers fed a control + urea ration. Cold-flo corn silage was more stable in air than control or Ensila Plus silages. No heating or molding was observed in Cold-flo silage after 28 days of air exposure; control silage heated after 10 days; Ensila Plus after 8 days. Dry matter removed from the silos and fed was similar for control (93.3%) and Ensila Plus (94.1%) silages, but only 88.55% of the Cold-flo silage was removed and fed. When fermentation, storage, and feedout losses were combined with steer performance, one ton of control silage (supplemented with SBM) produced 2.1 lbs. more gain than one ton of Ensila Plus silage (93.7 vs. 91.6 lbs.) and 9.5 lbs. more gain than one ton of Cold-flo silage (93.7 vs. 84.2 lbs.). Control silage supplemented with urea produced 85.8 lbs. of gain per ton.
Keywords: Beef; Ensila plus; Cold-flo additives; Corn silage